Proceedings of the IEEE 2001 International Interconnect Technology Conference (Cat. No.01EX461) 2001
DOI: 10.1109/iitc.2001.930007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of electroless copper as a seed layer for sub-0.1 /spl mu/m interconnects

Abstract: Complete gapfill of 0.1 pm features with electroless Cu seed layers and electroplated Cu was demonstrated. Electrical tests on test structures indicated similar line and via chain resistance, yield and line-to-line leakage current on wafers with electroless Cu seed and PVD Cu seed layers filled with electroplated Cu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[3][4][5] Gandikota et al and Andryuschenko and Reid reported that high-aspect via holes were filled completely by electroplating on a Cu seed layer prepared by physical vapor deposition ͑PVD͒ followed by repair by electroless copper plating. 7,8 However, the processes proved to be too complicated for practical manufacturing.…”
mentioning
confidence: 99%
“…[3][4][5] Gandikota et al and Andryuschenko and Reid reported that high-aspect via holes were filled completely by electroplating on a Cu seed layer prepared by physical vapor deposition ͑PVD͒ followed by repair by electroless copper plating. 7,8 However, the processes proved to be too complicated for practical manufacturing.…”
mentioning
confidence: 99%